2022
DOI: 10.21037/atm-22-526
|View full text |Cite
|
Sign up to set email alerts
|

New prognostic biomarker CMTM3 in low grade glioma and its immune infiltration

Abstract: Background: The CKLF-like MARVEL transmembrane domain-containing 3 (CMTM3) is differentially expressed in a variety of tumors and closely related to tumor occurrence and progression. The expression of CMTM3 was significantly elevated in glioma compared with normal brain tissue, to explore the potential function of CMTM3 in the prognosis and immune infiltration of glioma has certain clinical significance. Methods:The tumor data in this study were derived from the sequencing data of various tumors in The Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Most patients with LGG inevitably progress to high-grade glioma (HGG) ( Duffau, 2018 ). Various treatment methods, such as surgery, radiotherapy, chemotherapy, immunotherapy, electric field therapy, and neutron therapy are used, but tumor recurrence appears to be unavoidable ( Lu et al, 2021 ; Li et al, 2022 ). Therefore, it is urgent to identify novel potential therapeutic targets for LGG.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with LGG inevitably progress to high-grade glioma (HGG) ( Duffau, 2018 ). Various treatment methods, such as surgery, radiotherapy, chemotherapy, immunotherapy, electric field therapy, and neutron therapy are used, but tumor recurrence appears to be unavoidable ( Lu et al, 2021 ; Li et al, 2022 ). Therefore, it is urgent to identify novel potential therapeutic targets for LGG.…”
Section: Introductionmentioning
confidence: 99%
“…Although standard treatment is available, LrGG generally transforms into high‐grade glioma within 4–5 years after diagnosis 28 . Owing to the significant heterogeneity of LrGG, patients are often resistant to conventional treatment 29,30 . Consequently, prognosis prediction and individualized treatment strategies are difficult to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…28 Owing to the significant heterogeneity of LrGG, patients are often resistant to conventional treatment. 29,30 Consequently, prognosis prediction and individualized treatment strategies are difficult to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that CMTM3 was significantly associated with a variety of immune cells in the immune microenvironment, such as macrophages and dendritic cells in high-grade gliomas, and was also associated with prognosis. High expression of CMTM3 was associated with a poorer prognosis [42]. Fan et al reported that Pfn-1 phosphorylation is involved in the regulation of endothelial vasculin expression and promotes abnormal vascularization and GBM development through a hypoxy-independent HIF-1α induction mechanism [43].…”
Section: Discussionmentioning
confidence: 99%